PHD-finger family genes in wheat (Triticum aestivum L.): Evolutionary conservatism, functional diversification, and active expression in abiotic stress - Pang, Fei; Niu, Junqi; Solanki, Manoj Kumar; Nosheen, Shaista; Liu, Zhaoliang; Wang, Zhen (Frontiers in Plant Science, 2022)
Plant homeodomain (PHD) transcription factors (TFs) are a class of proteins with conserved Cys4-His-Cys3 domains that play important roles in plant growth and development, and in response to abiotic stresses. Although characterization of PHDs have been performed in plants, little is known about their function in wheat (Triticum aestivum L.), especially under stress conditions. In the present study, 244 TaPHDs were identified in wheat using comparative genomics. We renamed them TaPHD1-244 based on their chromosomal distribution, and almost all PHD proteins were predicted to be located in the nucleus. According to the unrooted neighbor-joining phylogenetic tree, gene structure, and motif analyses, PHD genes were divided into four clades. A total of 149 TaPHD genes were assigned to arise from duplication events. Furthermore, 230 gene pairs came from wheat itself, and 119, 186, 168, 7, 2, and 6 gene pairs came from six other species (Hordeum vulgareto, Zea mays, Oryza sativa, Arabidopsis thaliana, Brassica rapa, and Gossypium raimondii, respectively). A total of 548 interacting protein branches were identified to be involved in the protein interaction network. Tissue-specific expression pattern analysis showed that TaPHDs were highly expressed in the stigma and ovary during flowering, suggesting that the TaPHD gene plays an active role in the reproductive growth of wheat. In addition, the qRT-PCR results further confirmed that these TaPHD genes are involved in the abiotic stress response of wheat. In conclusion, our study provides a theoretical basis for deciphering the molecular functions of TaPHDs, particularly in response to abiotic stress.